Efficacy and safety of anlotinib plus XELOX regimen as first-line therapy for mCRC: a single-arm, multicenter, phase II study (ALTER-C-001) - Song, Bo; Hu, Hai; Zhang, Li; Ye, Su-Juan; Jin, Yong-Dong; Shang, Chang-Ling; Zhang, Jun; Sun, Hao; Zhang, Ke; Yi, Bo; Han, Yun-Wei; Yan, Jin (Frontiers in Oncology, 2023)
Background: Anlotinib showed encouraging anti-tumor activity in metastatic colorectal cancer (mCRC). This study was designed to assess the efficacy and safety of anlotinib plus XELOX as first-line therapy in mCRC patients.Eligible patients aged ≥18 with mCRC were enrolled in this multicenter, single-arm, phase II, exploratory study. Patients received at least 6 cycles of anlotinib, oxaliplatin, and capecitabine as initial therapy. Subsequently, patients received anlotinib monotherapy as maintenance therapy until tumor progression or intolerable toxicity. The primary endpoint was progression-free survival (PFS).Results: Thirty-one patients were included between December 2019 and March 2022. The median follow-up was 17.5 (95% CI, 3.0-17.5) months. The median PFS was 8.3 (95% CI, 6.3-10.0) months, with 6-and 12-month PFS rates of 82.3% (95% CI, 59.2%-93.0%) and 18.9% (95% CI, 4.8%-40.1%), respectively. Fifteen (48.4%) achieved partial response for an ORR of 48.4% (95% CI, 30.2%-66.9%). The disease control rate was 71.0% (95% CI, 52.0%-85.8%) due to 7 (22.6%) stable diseases. The median duration of response was 6.0 (95% CI, 3.6-8.0) months and 1 patient had the longest ongoing response of 17.3 months. Of 24 patients with evaluable imaging, 23 (74.2%) obtained tumor shrinkage. The median PFS (11.0 vs. 6.9 months) and ORR (66.7% vs. 60.0%) for patients with RAS/BRAF wild-type were numerically better than those with mutation. Three patients are still ongoing treatment. The grade 3 or more treatment-emergent adverse events (TEAEs) were mainly hypertension (12.9%) and decreased neutrophil count (12.9%). Four (12.9%) had serious TEAEs, primarily including abdominal pain and incomplete intestinal obstruction.Anlotinib plus XELOX as first-line therapy in patients with mCRC showed anti-tumor activity and safety profile, which is worth further investigation.